Cellular uptake of paraquat determines subsequent toxicity including mitochondrial damage in lung epithelial cells. (March 2019) - Kanno, Sanae; Hirano, Seishiro; Mukai, Toshiji; Ro, Ayako; Kato, Hideaki; Fukuta, Mamiko; Aoki, Yasuhiro
Highlights: Mitochondrial dysfunction might be responsible for the PQ-provoked toxicity. An accumulation ability of PINK1 by PQ is different between A549 and BEAS. A549 that are resistant to oxidative stress were more susceptible to PQ than BEAS. PQ concentration in A549 after exposure was higher than that in BEAS. The amount of ROS generated in A549 after PQ exposure was as low as that in BEAS. Abstract: Paraquat (PQ) is one of the commonly used herbicides in the world, despite its high toxicity. The ingestion of PQ accidentally or intentionally causes severe damage in diverse organs including the lung. Pulmonary fibrosis triggered by PQ accumulation in the lung epithelial cells is one of the major causes of death. This study investigated the intracellular accumulation of PQ, reactive oxygen species (ROS) generation and mitochondrial injury using two lung epithelial cell lines A549 and BEAS-2B (BEAS). Although A549 exhibit greater resistance to oxidative stress than BEAS, a cytotoxicity assay for PQ demonstrated that EC50 for lethality in A549 was 7 times lower than that in BEAS. When exposed to PQ at a concentration around EC50 for lethality, the amount of ROS generated in A549 was as low as that in BEAS. Conversely, the cellular concentration of PQ in A549 after exposure was higher than that in BEAS, which suggests a distinct difference in the susceptibility to PQ between these cell lines. After a 16 h exposure to PQ, mitochondrial membrane potential (MMP) decreased in A549, but decreased only slightly in BEAS even following a 30 h exposure. PQ-exposed A549 reduced an accumulation of PTEN-induced kinase 1 (PINK1), which works in degradation of damaged mitochondria, following the decrease of MMP, whereas PQ did not decline the PINK1 in BEAS. These results suggest that mitochondrial dysfunction due to cellular accumulation of PQ might contribute to the PQ-provoked toxicity more than the ROS generation in the lung epithelial cells.